Covid- 19 Outbreak: Opportunity or Risk for Gig Economy Workers - Nazruzila Razniza, Mohd Nadzri; Kamal Halili, Hassan (INTI International University, 2020)
The services of gig economy workers especially delivery riders are tremendously demanded recently due to the enforcement of movement control order (the MCO). They can easily resolve the affairs of getting ready- to-eat-meal, groceries, wet stuff to customers’ doorstep in return of a certain rate of service charge. Nevertheless, behind these overwhelming opportunities of daily tasks comparing to previous days before the MCO, eventually, they double up the risk to be infected with Covid-19. Unfortunately, as an independent contractor who depends largely on some tasks secured daily, it is relatively reasonable to describe gig economy workers as vulnerable labour. Therefore, this article aims to investigate the position of gig economy workers in the purview of the existing Malaysian employment legal framework. Their position is assessed with reference to the recent scenario of the Covid-19 outbreak that is taking place locally and globally to eventually disclose the role and function of this category of labour who are considerably neglected. In the meantime, the author identifies a few issues that are commonly encountering by these workers mainly the implication of their status as ‘independent contractor’ or ‘self-employed’ within the employment legislative framework. The author presents examples within the UK and US jurisdictions to demonstrate their role, challenge, issue, and position in the legal perspective.